Effects of calcium peroxide or biochar-enzyme feed additives on milk production, enteric methane emissions, and ruminal microbiota in Nordic Red dairy cows - Vattulainen, Jenni; Bayat, Ali-Reza; Stefański, Tomasz; Rinne, Marketta; Tapio, Ilma (Elsevier, 2025)
Expanded basic research is needed to discover and develop wider selection of dietary additives that are economically feasible without compromising animal performance or health. The objective of this study was to evaluate the effect of 2 feed additives as methane-mitigating agents in milk production systems. Four multiparous Nordic Red dairy cows were assigned to a 4 × 4 Latin square experiment with four 28-d periods using respiration chambers. The control diet (CON) consisted of grass silage and dietary concentrates mixed at forage-to-concentrate ratio of 65:35 on DM basis. The 3 experimental treatments consisted of the CON diet supplemented with 0.2% of biochar with fibrolytic enzymes and live yeast additive (BFE) or with 0.75% or 1.5% CaO2 on a DM basis (CaPe1 and CaPe2, respectively). Calcium peroxide (CaPe) was included in the concentrate pellet; the mixture of biochar, fibrolytic enzymes and live yeast was added to the diet during TMR preparation; and diets were fed as TMR 4 times daily. Feeding BFE had minor effect on the parameters evaluated in the experiment. Feeding CaPe resulted in linear reductions in DMI, OMI, CP, ether extract (EE), NDF, and gross energy (GE) intake compared with CON. Yields of milk, ECM, fat, protein, lactose and total solids decreased linearly, but milk composition and SCC were not affected. Apparent total-tract digestibilities of DM, OM, CP, EE, NDF, and GE decreased linearly, whereas excretion of Ca and P in feces increased linearly with increasing CaPe level. We found that CaPe1 tended to decrease the molar proportion of acetate and increased that of propionate, whereas butyrate increased linearly. Dietary CaPe inclusion decreased daily CH4 production (g/d) linearly by 15.0%, but CH4 yield (g/kg DM or OM intake) and intensity (g/kg milk or ECM) were not affected. Hydrogen production (g/d) and yield (g/kg DMI) decreased at CaPe1 but plateaued at CaPe2. Feeding CaO2 increased richness of ciliate protozoa and influenced rumen bacteria and ciliate protozoa community structure. No such effect was observed on archaea or anaerobic fungi. The feed additives BFE and CaPe were not effective CH4-mitigating agents under the conditions of the present experiment.
Keywords: grass silage; feed additives; greenhouse gases; microbiome; respiration chambers